Izpodbijanje sklepa o povečanju osnovnega kapitala - Jurgec, Lovro (Podjetje in delo, 2016)
A general meeting's resolution on the increase of share capital may be contested on the grounds of the general contestable reasons pursuant to Article 395 of ZGD-1 and on the grounds of a special contestable reason pursuant to paragraph 2 of Article 400 of ZGD-1. This paper analyses the aforementioned special contestable reason enacted in paragraph 2 of Article 400 of ZGD-1, which determines that in the case of exclusion of pre-emptive right of existing shareholders, the resolution on the increase of share capital may be contested also if the issue price of the newly issued shares is, in the resolution on the increase of share capital, determined disproportionally low. For the purposes of comprehensibility, this paper also makes a distinction between the aforementioned special contestable reason from paragraph 2 of Article 400 of ZGD-1 and contesting the general meeting's resolution due to an unlawfully executed legal squeeze-out and contesting the general meeting's resolution due to an economic squeeze-out.
Keywords: gospodarske družbe; kapital; odločanje; povečanje; pravna ureditev; vodenje